2019
DOI: 10.1093/rheumatology/kez282
|View full text |Cite
|
Sign up to set email alerts
|

IL-18 as a biomarker linking systemic juvenile idiopathic arthritis and macrophage activation syndrome

Abstract: Objectives Systemic juvenile idiopathic arthritis (sJIA) is a childhood arthritis with features of autoinflammation and high risk of macrophage activation syndrome (MAS). IL-18 has been shown to have key roles in sJIA and MAS. We aimed to examine IL-18 levels in sJIA in relation to disease activity and history of MAS and other disease biomarkers namely S100 proteins and CXCL9. Methods Total IL-18, CXCL9 and S100 proteins leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 18 publications
2
74
1
3
Order By: Relevance
“…Study characteristics are displayed in Table 1. Briefly, nine studies included MAS patients [15,16,18,20,23–27], eight included patients with sHLH of other causes [15,17,20,24,28–31] and six studies included pHLH [15,16,23,29–31]. Other inflammatory conditions included were EBV infection ( n = 5) [20,24,29–31], Kawasaki’s disease ( n = 2) [20,28], sJIA/AOSD ( n = 4) [18,20,25,26] and patients with other infectious, inflammatory or malignant disorders [15,17,23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study characteristics are displayed in Table 1. Briefly, nine studies included MAS patients [15,16,18,20,23–27], eight included patients with sHLH of other causes [15,17,20,24,28–31] and six studies included pHLH [15,16,23,29–31]. Other inflammatory conditions included were EBV infection ( n = 5) [20,24,29–31], Kawasaki’s disease ( n = 2) [20,28], sJIA/AOSD ( n = 4) [18,20,25,26] and patients with other infectious, inflammatory or malignant disorders [15,17,23].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies investigated patients with a history of recurrent MAS, and found that IL‐18 was significantly elevated in sJIA patients with history of MAS compared with sJIA with no history of MAS, regardless of whether or not the patients were in the active or inactive phase of sJIA [15,26,27].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies revealed some biomarkers including IL-18, CXCL9, neopterin and soluble tumor necrosis factor receptor type II might be useful for the prediction of the development of MAS and the diagnosis of the transition from active phase of s-JIA to MAS [14][15][16][17][18][19][20][21]. Recent studies revealed that high levels of free IL-18 (that is, IL-18 not bound to IL-18 binding protein) increases the risk of developing MAS [15,22].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its costimulatory functions on Th1 cytokines, IL-18 acts directly as a proinflammatory cytokine [ 46 ]. The level of IL-18 reportedly increased in both the serum and synovial fluid samples of RA patients [ 39 , 47 , 48 , 49 ], and IL-18-deficient mice were shown to have a reduced incidence and severity of arthritis in preclinical models [ 50 , 51 ]. IL-33, another proinflammatory cytokine that was shown to exacerbate inflammation in preclinical arthritis models [ 9 , 52 , 53 ] but that, at the same time, harbors direct effects on bone homeostasis [ 54 , 55 ], was significantly reduced in RA patients following short-term high-fiber dietary interventions.…”
Section: Discussionmentioning
confidence: 99%